Fine Particulate Matter and Total Mortality in Cancer Prevention Study Cohort Reanalysis - James E. Enstrom (SAGE Publishing, 2017)
Background: In 1997 the US Environmental Protection Agency (EPA) established the National Ambient Air Quality Standard (NAAQS) for fine particulate matter (PM 2.5 ), largely because of its positive relationship to total mortality in the 1982 American Cancer Society Cancer Prevention Study (CPS II) cohort. Subsequently, EPA has used this relationship as the primary justification for many costly regulations, most recently the Clean Power Plan. An independent analysis of the CPS II data was conducted in order to test the validity of this relationship. Methods: The original CPS II questionnaire data, including 1982 to 1988 mortality follow-up, were analyzed using Cox proportional hazards regression. Results were obtained for 292 277 participants in 85 counties with 1979-1983 EPA Inhalable Particulate Network PM 2.5 measurements, as well as for 212 370 participants in the 50 counties used in the original 1995 analysis. Results: The 1982 to 1988 relative risk (RR) of death from all causes and 95% confidence interval adjusted for age, sex, race, education, and smoking status was 1.023 (0.997-1.049) for a 10 µg/m 3 increase in PM 2.5 in 85 counties and 1.025 (0.990-1.061) in the 50 original counties. The fully adjusted RR was null in the western and eastern portions of the United States, including in areas with somewhat higher PM 2.5 levels, particularly 5 Ohio Valley states and California. Conclusion: No significant relationship between PM 2.5 and total mortality in the CPS II cohort was found when the best available PM 2.5 data were used. The original 1995 analysis found a positive relationship by selective use of CPS II and PM 2.5 data. This independent analysis of underlying data raises serious doubts about the CPS II epidemiologic evidence supporting the PM 2.5 NAAQS. These findings provide strong justification for further independent analysis of the CPS II data.